PERWUJUDAN GREEN ECONOMY MELALUI PREOGRAM PAWON URIP UNTUK MEMENUHI TUJUAN SDGs - Nurbadriyah, Anis (FORPIM PTKIS ZONA TAPAL KUDA, 2024)
The Pawon Urip program is an exciting initiative in realizing a green economy as part of efforts to achieve the Sustainable Development Goals (SDGs). Through this approach, it is expected to increase natural resource efficiency, minimize environmental impacts, and provide sustainable economic benefits. The objectives of the research on the realization of a green economy through the Pawon Urip program to meet the SDGs include evaluating the program's impact on environmental sustainability, analyzing its contribution to increasing food security (SDGs 2). This research uses a qualitative research method with a phenomenological approach. The results of this study refer to a shift towards more sustainable and environmentally friendly natural resource empowerment practices. This pawon urip program encourages economic growth that is not only materially beneficial, but also minimizes negative impacts on the environment.